Mejoras de flujos de procesos y diseño de matrices documentales para GADs parroquiales rurales de Chone - Zambrano Loor, Yeidy Selene (2024)
The research was oriented towards improving the flows and the design of the documentary matrices of the processes for the rural parish GADs of Chone, Ricaurte and Canuto. To achieve the objectives, three phases were used that are consistent with each specific objective: Firstly, the analysis of the legal and regulatory bases corresponding to the documentary processes was carried out, which made it possible to demonstrate the standards to which the GAD are governed, which are the general ones since they do not have their own standards, as well as the determinations. of the processes, in a second instance the reformulation of the flows was carried out, where it was necessary to identify the established flow diagrams and find the respective shortcomings based on the regulations, for these improvements were made through BPMN modeling (Business Process Modeling and Notation), thirdly, the respective design of the documentary matrices was given to support the executed flows. The results show the lack of internal regulations. In conclusion, in the Parochial Decentralized Autonomous Governments of Ricaurte and Canuto, the BPMN model for the preparation of the flowcharts of the processes that are systematized is unknown, which correspond to those established by the general regulations, given that these do not have internal regulations. for their realization.